Validating the Spanish translation of the posttraumatic stress disorder checklist (PCL-5) in a sample of individuals with traumatic brain injury - Haghish, E. F.; Sahuquillo, Juan; Radoi, Andreea; Pomposo, Ingio; Lozano, Guillermo Carbayo (Frontiers in Psychology, 2024)
There is controversy regarding the comorbidity of posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI). The present study translated the PTSD Checklist for to Spanish and validated it in a sample of patients with TBI six months after the injury. The study included 233 patients (162 males and 71 females) recruited from four Spanish hospitals within twenty-four hours of traumatic brain injury. A total of 12.2% of the sample met the provisional PTSD diagnostic criteria, and the prevalence was equal between male and female participants. The analysis confirmed the internal consistency of the translated instrument (α = 0.95). The concurrent validity of the instrument was confirmed based on high correlation coefficients of 0.7 and 0.74 with the General Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire (PHQ-9), respectively. Exploratory factor analysis also confirmed that the items on the PCL-5 can be differentiated from the GAD-7 and PHQ-9 items. Confirmatory factor analysis (CFA) was used to examine the structural validity of the Spanish translation of the PCL-5 with three different models. CFA partially confirmed the four-factor PTSD model, whereas both the six-factor anhedonia model and the seven-factor hybrid model showed adequate fit, thus confirming the structural validity of the translated instrument. However, the difference between the anhedonia and hybrid models was not statistically significant; moreover, both models showed signs of overfitting. Therefore, the utility of these models should be reexamined in future studies. Overall, the results suggest that the Spanish translation of the PCL-5 is a reliable and valid instrument for screening PTSD symptoms among Spanish TBI patients. The Spanish translation of the PCL-5 is also presented in the manuscript.